2021
DOI: 10.3390/app11031236
|View full text |Cite
|
Sign up to set email alerts
|

Weekly and Longitudinal Element Variability in Hair Samples of Subjects Non-Occupationally Exposed

Abstract: Hair is an ideal tissue for tracing the human health conditions. It can be cut easily and painlessly, and the relative clinical results can give an indication of mineral status and toxic metal accumulation following long-term or even acute exposure. Different authors have found outdoor pollution phenomena, such as the levels, significantly alter metal and metalloid hair contents. This paper investigates the element concentration variability in hair samples collected from a not-exposed teenager, neither environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Another broad area which is well represented in this special issue is environmental chemistry, with four featured articles. Avino et al [4] reported on the weekly and longitudinal elemental variability in hair samples collected from non-occupationally exposed subjects. Neutron activation analysis was used to determine 30 elements in hair samples collected from different locations on the scalp.…”
mentioning
confidence: 99%
“…Another broad area which is well represented in this special issue is environmental chemistry, with four featured articles. Avino et al [4] reported on the weekly and longitudinal elemental variability in hair samples collected from non-occupationally exposed subjects. Neutron activation analysis was used to determine 30 elements in hair samples collected from different locations on the scalp.…”
mentioning
confidence: 99%